Tourism Promotion Strategy in Banyuwangi (2012-2021) - Aisya, Nadin; Yuliati , Yuliati (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2024)
The purpose of this research is to find out about the promotional strategies used by Banyuwangi Regency in developing tourism in Banyuwangi, a district located at the eastern tip of Java Island from 2012 to 2021. Tourism in Banyuwangi itself covers land, sea, and mountains located from north to south. This writing uses historical methods using primary sources and secondary sources. Sources that support this writing include books, photos, newspapers, and scientific articles. The results of this paper's study show that the development of tourism in Banyuwangi for approximately 10 years has increased quite significantly. This can be seen from how the Banyuwangi Regency government participates in efforts to advance tourism development in Banyuwangi.